Slipcasting of MAX phase tubes for nuclear fuel cladding applications. (January 2020) - Galvin, T.; Hyatt, N.C.; Rainforth, W.M.; Reaney, I.M.; Shepherd, D.
Highlights: Ti3 SiC2 tubes cast from slips with polyethyleneimine and methylcellulose additives. Tubes were sintered under vacuum at 1450 °C with a 2 h dwell. Strongest tube achieved a hoop stress per thickness of 9.07 ± 2.16 MPa/mm at rupture. Abstract: As a proof of concept, tubes of Ti3 SiC2 MAX phase were slipcast in order to investigate its potential for the fabrication of fuel cladding for nuclear reactors. A slip consisting of 46% dry weight basis (dwb) water, 4% dwb polyethyleneimine (PEI), 0.5% dwb methylcellulose was used to cast the tubes, which were then sintered for 2 h under vacuum at 1450 °C. Silicon loss was observed at surface which resulted in the formation of TiC. The hoop stress to destruction of the tubes was measured and achieved a maximum of 9.1 ± 2.2 MPa/mm of tube thickness.